CFD analysis of air intake system of 1.6 l Proton Waja engine by adding guide vanes - Vijayakumar, Marimuthu (2010)
The objective of the current research was to analyze the flow through the air intake system of 1.6L Proton Waja engine by adding guide vane. The pressure drop across the air intake system is known to have a significant influence on the indicated power of the SI engine. The pressure drop along the intake system is proportional to the engine speed and cross sectional area. The guide vane is placed in the system to reduce the pressure drop across the system. It was found that the guide vane help to reduce pressure drop across the air intake system where it increases the capabilities of air induction system to suck more air to the engine. The geometry of air intake system of Proton Waja 1.6L engine was used in the modeling approach. The study was focused on different engine speed. This analysis was done in CFD using a model setup with appropriate speed of the Proton Waja 1.6L engine from maximum speed to minimum speed. The CFD results of air intake system with the guide vane are validated against the CFD result of real air intake system of Proton Waja 1.6L which do not have guide vane.